Assessment of Seismic Vulnerability and Retrofit Strategies of a Historic Building on the Great Silk Road Based on its Current Condition Captured by Laser Scans. Issue 1 (2nd January 2019) - Takhirov, Shakhzod M.; Gilani, Amir; Quigley, Brian; Myagkova, Liliya
ABSTRACT: The technology of high-definition laser scanning is an essential tool for accurate non-destructive 3D measurements of structures. The research team used this technology and conducted an extensive laser-scanning program of many historic monuments in Uzbekistan. The program started in 2013 from scanning the famous Registan ensemble in Samarkand. Later in 2015, it was expanded to more cities and monuments and the laser scanning was conducted in Tashkent, Bukhara, Samarkand, and Shakhrisyabz. The monuments are from the Timurid Dynasty era and they are on the UNESCO World Heritage List. As a representative example, the research results obtained in Shakhrisabz (Uzbekistan) are discussed in detail. The Kok Gumbaz (Blue Dome) Mosque was scanned. It was built in 1437 and underwent several restorations and reinforcement efforts. A detailed finite element model of the monument was generated from the as-found geometry captured by laser scans. The physical properties of the monument were investigated by material tests. Based on the results of numerical simulations, recommendations on further reinforcement of the historic monument were developed.